Replicating Elite Dominance in Intangible Cultural Heritage Safeguarding: The Role of Local Government–Scholar Networks in China. Issue 1 (3rd March 2016) - Maags, Christina; Holbig, Heike
Abstract: Since "intangible cultural heritage" (ICH) became the new focal point in the global heritage discourse, governments and scholars in many countries have begun to promote this new form of "immaterial" culture. The People's Republic of China has been one of the most active state parties implementing the new scheme and adapting it to domestic discourses and practices. Policies formulated at the national level have become increasingly malleable to the interests of local government-scholar networks. By conducting a comparative case study of two provinces, this article aims to identify the role of local elite networks in the domestic implementation of the 2003 Convention for the Safeguarding of Intangible Cultural Heritage, focusing on the incentives of scholars and officials to participate in ICH policy networks. It finds that the implementation of the Convention has not removed the power asymmetry between elite and popular actors but, instead, has fostered an elite-driven policy approach shaped by symbiotic, mutually legitimizing government–scholar networks.